Artificial leather, its manufacturing method and its uses
By integrating a polyurethane with hydrophilic groups into the manufacturing process of artificial leather, which involves intertwining nonwoven and woven fabrics, the challenges of achieving strength, flexibility, and abrasion resistance are addressed, resulting in a high-performance, environmentally friendly artificial leather product.
Patent Information
- Application Number
- JP2024539945
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-07-19
- Filing Date
- 2024-06-17
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-06-17
AI Technical Summary
Existing methods for producing artificial leather with intertwined or integrated woven fabrics face challenges in achieving a balance between strength, flexibility, and abrasion resistance, particularly when using water-dispersed polyurethane, which often results in a stiff texture due to dense adhesion between the fabric and polyurethane.
The development of artificial leather comprising a fibrous base material formed by intertwining nonwoven and woven fabrics, combined with a polyurethane having hydrophilic groups. The polyurethane content is between 15% to 25% by mass, and is specifically attached to 10% to 80% of the outermost filaments of the multifilament, using a manufacturing process that includes entwining fabrics, impregnating with a polyurethane dispersion, and subsequent treatment to achieve the desired texture.
This approach results in artificial leather with high strength, excellent flexibility, and superior abrasion resistance, while also being manufactured using an environmentally friendly process that avoids organic solvents.
Smart Images

Figure 0007648011000002 
Figure 0007648011000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an artificial leather, a method for producing the same, and uses thereof. [Background technology]
[0002] Artificial leather, which is mainly composed of a fibrous base material such as nonwoven fabric and polyurethane, has excellent characteristics not found in natural leather, such as high durability and uniformity, and in particular, so-called suede-like artificial leather, in which the surface is buffed to form naps of ultrafine fibers, is used not only as a material for clothing but also in various fields such as vehicle interior materials, furniture interior materials, and building materials. In particular, from the viewpoint of environmental consideration, a method of using a water-dispersed polyurethane in which a polyurethane resin is dispersed in water, instead of a method of using a conventional organic solvent-based polyurethane as the polyurethane, has been widely studied.
[0003] When suede-like artificial leather is used as a covering material for vehicle interiors, etc., repeated long-term use can cause distortion in the covering material. Therefore, methods are being investigated for integrating a woven fabric into the interior of a nonwoven fabric or on one side of the fabric to produce artificial leather that is strong and can withstand long-term use.
[0004] However, artificial leathers in which woven fabrics are integrated into the interior or one side of a nonwoven fabric generally have the problem of being stiff in texture, one of the main reasons being that the polyurethane applied strongly grips the intertwining points of the woven fabric, reducing the flexibility of the woven fabric.
[0005] In particular, when a water-dispersed polyurethane is used as the polyurethane and the polyurethane emulsion is coagulated by flocculating it with heat, the polyurethane membrane structure becomes a dense, non-porous membrane, so that the adhesion between the fabric and the polyurethane becomes dense and the entangled portions of the fibers that make up the fabric are tightly gripped, resulting in a significantly harder texture.
[0006] In view of this situation, several methods have been proposed for obtaining artificial leather having high strength and excellent flexibility by using water-dispersible polyurethane in artificial leather in which a woven fabric is integrated inside or on one side of a nonwoven fabric.
[0007] For example, Patent Documents 1 and 2 propose a method in which a specific amount of polyvinyl alcohol having a specific degree of saponification and polymerization is applied to a fibrous substrate, then a water-dispersible polyurethane is applied, and then the polyvinyl alcohol is removed. It is described that this method achieves an elegant appearance and soft feel, and further provides a sheet-like material having good abrasion resistance.
[0008] Patent Document 3 also describes that by setting the ratio of polyurethane resin to 100% by mass of the fiber sheet to 20% by mass or less, a soft texture can be achieved even in artificial leather that contains a scrim, which is a woven or knitted fabric, and uses a water-dispersible polyurethane resin. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2013-234409 A [Patent Document 2] International Publication No. 2014 / 042241 [Patent Document 3] International Publication No. 2020 / 054256 Summary of the Invention [Problem to be solved by the invention]
[0010] In the methods disclosed in Patent Documents 1 and 2, polyvinyl alcohol is applied before polyurethane is applied to coat the woven or knitted fabric, and is removed after polyurethane is applied, thereby preventing direct adhesion between the polyurethane and the woven or knitted fabric and achieving a soft texture. However, since a process for eluting polyvinyl alcohol is required, there is room for improvement in terms of production efficiency.
[0011] In the method disclosed in Patent Document 3, the amount of polyurethane applied is small, and it is difficult to say that the method satisfies the level required by the market in terms of abrasion resistance.
[0012] In view of the above problems, an object of the present invention is to provide an artificial leather containing a fiber-entangled body consisting of a nonwoven fabric and a woven fabric as a constituent component, which is produced by an environmentally friendly process that does not use organic solvents, and which combines a soft feel with excellent abrasion resistance, and a method for producing the same. [Means for solving the problem]
[0013] In order to solve the above problems, the present invention has the following configuration. [1] An artificial leather comprising a fibrous base material formed by entangling and integrating a nonwoven fabric and a woven fabric, and a polyurethane having a hydrophilic group, The nonwoven fabric is composed of polyester ultrafine fibers having an average single fiber diameter of 0.1 μm or more and 10.0 μm or less, The woven fabric is composed of a multifilament having 30 to 300 filaments, and the average single fiber diameter of the filaments constituting the multifilament is 1 μm to 30 μm, The content of the polyurethane in the artificial leather is 15% by mass or more and 25% by mass or less, and the ratio of filaments to which the polyurethane is attached among the outermost filaments of the multifilament is 10% or more and 80% or less. Artificial leather.
[0014] [2] The artificial leather according to [1], wherein the polyurethane is a polyether-based polyurethane and / or a polycarbonate-based polyurethane.
[0015] [3] A method for producing an artificial leather according to [1], comprising the following steps (1) to (3) in this order: (1) A process of entangling and integrating a nonwoven fabric made of ultrafine fiber-developing fibers with a woven fabric to form a fibrous base material. (2) A process for obtaining a shrunk sheet having a width of 0.85L or more and 0.95L or less, when the width of the fibrous base material before impregnation is L, by impregnating the fibrous base material with an aqueous dispersion of polyurethane having a hydrophilic group and then coagulating the polyurethane to obtain a sheet. (3) A step of producing polyester ultrafine fibers from the ultrafine fiber-producing fibers of the shrink sheet.
[0016] [4] The method for producing an artificial leather according to [3], wherein the entanglement and integration means in the step (1) is a needle punching process.
[0017] [5] The method for producing an artificial leather according to [3] or [4], wherein the means for obtaining the shrink sheet in the step (2) is a dry heat treatment at an atmospheric temperature of 100°C or higher and 180°C or lower.
[0018] [6] The method for producing an artificial leather according to any one of [3] to [5], wherein the means for developing the polyester ultrafine fibers in the step (3) is an alkali treatment.
[0019] [7] An automobile interior material comprising the artificial leather described in [1] or [2].
[0020] [8] An automobile part comprising the artificial leather described in [1] or [2].
[0021] [9] A seat comprising the artificial leather described in [1] or [2]. Effect of the Invention
[0022] According to the present invention, in an artificial leather comprising a fibrous base material in which a nonwoven fabric and a woven fabric are entangled and integrated, and a water-dispersible polyurethane, it is possible to obtain an artificial leather having high strength, excellent flexibility and abrasion resistance by a simple process. [Brief description of the drawings]
[0023] [Figure 1]This is a schematic cross-sectional view of a scanning electron microscope (SEM) photograph of an artificial leather cross section taken to measure and calculate the proportion of filaments to which polyurethane is attached among the outermost filaments of a multifilament. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The artificial leather of the present invention is an artificial leather comprising a fibrous base material formed by entangling and integrating a nonwoven fabric and a woven fabric, and a polyurethane having a hydrophilic group, The nonwoven fabric is composed of polyester ultrafine fibers having an average single fiber diameter of 0.1 μm or more and 10.0 μm or less, The woven fabric is composed of a multifilament having 30 to 300 filaments, and the average single fiber diameter of the filaments constituting the multifilament is 1 μm to 30 μm, The content of the polyurethane in the artificial leather is 15% by mass or more and 25% by mass or less, Furthermore, the ratio of the filaments to which the polyurethane is attached to the outermost filaments of the multifilament is 10% or more and 80% or less.
[0025] These components are described in detail below, but the present invention is not limited to the scope described below as long as it does not exceed the gist of the invention, and various modifications are possible without departing from the gist of the invention.
[0026] [Polyester microfiber] The artificial leather of the present invention has a fibrous base material, which is one of the components, composed of polyester ultrafine fibers having an average single fiber diameter of 0.1 μm to 10.0 μm. Note that "polyester ultrafine fibers" refers to "ultrafine fibers made of polyester resin" described below, and ultrafine fibers refer to "fibers having a single fiber diameter of 0.1 μm to 10.0 μm" measured and calculated by the method described below.
[0027] In this invention, the term "polyester resin" refers to a resin in which the molar fraction of the polyester unit in the repeating unit is 80 mol % to 100 mol %. Unless otherwise specified, the term "··-based resin" has the same meaning. This polyester resin can be used to make artificial leather with excellent heat resistance, light resistance, etc., and specific examples thereof include polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, and mixtures of these polyester resins and copolymers of these polyesters. The polyester resin can be obtained, for example, from a dicarboxylic acid and / or its ester-forming derivative and a diol.
[0028] Examples of the dicarboxylic acid and / or its ester-forming derivative used in the polyester resin include terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, diphenyl-4,4'-dicarboxylic acid and its ester-forming derivative. The ester-forming derivative in the present invention is a lower alkyl ester, an acid anhydride, an acyl chloride, etc. of a dicarboxylic acid. Specifically, methyl ester, ethyl ester, hydroxyethyl ester, etc. are preferably used. A more preferred embodiment of the dicarboxylic acid and / or its ester-forming derivative used in the present invention is terephthalic acid and / or its dimethyl ester.
[0029] Examples of diols that can be used in the polyester resin include ethylene glycol, 1,3-propanediol, 1,4-butanediol, cyclohexanedimethanol, etc. Among these, ethylene glycol is preferably used.
[0030] The polyester resin may contain inorganic particles such as titanium oxide particles, lubricants, pigments, heat stabilizers, ultraviolet absorbers, conductive agents, heat storage agents, antibacterial agents, and the like depending on various purposes.
[0031] The cross-sectional shape of the polyester ultrafine fiber may be either a round cross section or an irregular cross section. Specific examples of the irregular cross section include an ellipse, a flattened shape, a polygon such as a triangle, a sector shape, a cross shape, and the like.
[0032] In the present invention, the average single fiber diameter of the polyester ultrafine fibers is 0.1 μm or more and 10.0 μm or less. By making the average single fiber diameter of the polyester ultrafine fibers 10.0 μm or less, preferably 7.0 μm or less, more preferably 5.0 μm or less, the artificial leather can be made more flexible. In addition, the quality of the nap can be improved. On the other hand, by making the average single fiber diameter of the polyester ultrafine fibers 0.1 μm or more, preferably 0.3 μm or more, more preferably 0.7 μm or more, the artificial leather can be made to have excellent color development after dyeing when dyeing. In addition, when performing a nap raising treatment by buffing, the ease of dispersion and ease of handling of the polyester ultrafine fibers present in a bundle shape can be improved.
[0033] The single fiber diameter and average single fiber diameter of the polyester ultrafine fiber in the present invention are measured and calculated by the following method. (1) The cross section of the obtained artificial leather cut in the thickness direction is observed using a scanning electron microscope (SEM, Keyence Corporation's "VHX-D500 / D510" or a scanning electron microscope with equivalent performance). (2) The fiber diameters of 50 random polyester ultrafine fibers within the observation area are measured in three directions on the cross section of each polyester ultrafine fiber. However, when polyester ultrafine fibers with an irregular cross section are used, the cross-sectional area of a single fiber is first measured, and the diameter of a circle having that cross-sectional area is calculated using the following formula. The diameter thus obtained is the single fiber diameter of that single fiber.
[0034] Single fiber diameter (μm) = (4 × (cross-sectional area of single fiber (μm 2 )) / π) 1 / 2 (3) The arithmetic mean value (μm) of the 150 points obtained in total is calculated and rounded off to one decimal place to obtain the average single fiber diameter (μm) of the polyester ultrafine fiber.
[0035] [fabric] It is important that the woven fabric used in the artificial leather of the present invention is composed of multifilaments. As the component constituting the multifilaments, polyester-based resins or polyamide-based resins can be used, but it is preferable to use polyester-based resins, which are excellent in durability and heat resistance.
[0036] It is important that the average single fiber diameter of the filaments constituting the multifilament is 1 μm or more and 30 μm or less. By making the average single fiber diameter 30.0 μm or less, more preferably 15.0 μm or less, and even more preferably 13.0 μm or less, the artificial leather has excellent flexibility. On the other hand, by making the average single fiber diameter 1.0 μm or more, more preferably 8.0 μm or more, and even more preferably 9.0 μm or more, the shape stability of the product as artificial leather is improved.
[0037] In the present invention, the average single fiber diameter of the filaments constituting the multifilament is calculated by taking a scanning electron microscope (SEM) photograph of the cross section of the artificial leather, randomly selecting 10 filaments from the multifilament constituting the woven fabric, measuring the single fiber diameters of the filaments, calculating the arithmetic average of the 10 filaments, and rounding off to the nearest tenth. However, when a filament with a modified cross section is used, the cross-sectional area (μm 2 ) and calculate the diameter when the cross section is considered to be a circle, i.e., the equivalent circle diameter, to determine the filament diameter (μm).
[0038] It is important that the number of single fibers contained in the multifilament constituting the woven fabric, i.e., the number of filaments, is 30 or more and 300 or less. By making the number of filaments 30 or more, more preferably 50 or more, not only is the shape stability of the product as artificial leather improved, but also, when the nonwoven fabric and the woven fabric are entangled and integrated by needle punching or the like, the fibers constituting the woven fabric are less likely to be exposed on the surface of the artificial leather, which is preferable. On the other hand, by making the number of filaments 300 or less, more preferably 250 or less, and even more preferably 100 or less, the artificial leather has excellent flexibility. In this case, the number of filaments of the warp thread and the number of filaments of the weft thread may be the same or different.
[0039] Furthermore, the twist number of the multifilament is preferably 1,000 to 4,000 T / m. By setting the twist number to 4,000 T / m or less, more preferably 3,500 T / m or less, and even more preferably 3,000 T / m or less, an artificial leather with excellent flexibility can be obtained, and by setting the twist number to 1,000 T / m or more, more preferably 1,500 T / m or more, and even more preferably 2,000 T / m or more, damage to the fibers constituting the woven fabric can be prevented when the nonwoven fabric and the woven fabric are entangled and integrated by needle punching or the like, and the mechanical strength of the artificial leather is excellent, which is preferable.
[0040] The basic weave of the fabric may be twill or satin, but a plain weave, which is less prone to misalignment, is preferably used.
[0041] The weave density of the woven fabric is preferably adjusted so that both the warp and weft threads in the artificial leather are 40 threads / 2.54 cm to 200 threads / 2.54 cm. By setting the weave density of the woven fabric constituting the artificial leather to 40 threads / 2.54 cm or more, more preferably 60 threads / 2.54 cm or less, an artificial leather with excellent shape stability can be obtained. On the other hand, by setting the weave density of the woven fabric constituting the artificial leather to 200 threads / 2.54 cm or less, more preferably 150 threads / 2.54 cm or less, not only can the texture of the artificial leather be made soft, but also the entanglement of the fibers of the nonwoven fabric is not hindered when the nonwoven fabric and the woven fabric are entangled and integrated, and as a result, fiber shedding of the artificial leather can be suppressed.
[0042] [Fiber base material] The fibrous base material used in the present invention is formed by entangling and integrating the nonwoven fabric made of the above-mentioned polyester ultrafine fibers and the above-mentioned woven fabric.
[0043] [Polyurethane with hydrophilic groups] Next, the artificial leather of the present invention contains polyurethane having a hydrophilic group as a constituent element. The details of this will be described in further detail below.
[0044] (1) Polyurethane with hydrophilic groups First, in the present invention, "having a hydrophilic group" refers to "having a group having active hydrogen". Specific examples of the group having active hydrogen include a hydroxyl group, a carboxyl group, a sulfonic acid group, an amino group, etc., and from the viewpoint of reactivity with a crosslinking agent having a carbodiimide group described later, it is preferable that the compound has a hydroxyl group or a carboxyl group.
[0045] The polyurethane having a hydrophilic group can be obtained by reacting a polymer polyol described later, an organic diisocyanate, and an active hydrogen component-containing compound having a hydrophilic group to form a hydrophilic prepolymer, and then adding and reacting a chain extender to obtain a polyurethane precursor, which is then reacted with a crosslinking agent. These will be described in detail below.
[0046] (1-1) Polymer polyol Examples of the polymer polyol preferably used in the synthesis of the polyurethane include polyether polyols, polyester polyols, and polycarbonate polyols.
[0047] First, examples of polyether polyols include polyols obtained by addition polymerization of monomers such as ethylene oxide, propylene oxide, butylene oxide, styrene oxide, tetrahydrofuran, epichlorohydrin, and cyclohexylene using polyhydric alcohols or polyamines as initiators, and polyols obtained by ring-opening polymerization of the above-mentioned monomers using protonic acids, Lewis acids, cationic catalysts, etc. as catalysts. Specific examples include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc., and copolymer polyols combining these.
[0048] Examples of polyester polyols include polyester polyols obtained by condensing various low molecular weight polyols with polybasic acids, and polyols obtained by depolymerization of lactones.
[0049] Examples of low molecular weight polyols used in polyester polyols include linear alkylene glycols such as ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1.8-octanediol, 1,9-nonanediol, and 1,10-decanediol, branched alkylene glycols such as neopentyl glycol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, and 2-methyl-1,8-octanediol, alicyclic diols such as 1,4-cyclohexanediol, and aromatic dihydric alcohols such as 1,4-bis(β-hydroxyethoxy)benzene. In addition, adducts obtained by adding various alkylene oxides to bisphenol A can also be used as low molecular weight polyols.
[0050] On the other hand, examples of the polybasic acid used in the polyester polyol include one or more selected from the group consisting of succinic acid, maleic acid, adipic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, phthalic acid, isophthalic acid, terephthalic acid, and hexahydroisophthalic acid.
[0051] Examples of the polycarbonate-based polyol include compounds obtained by reacting a polyol with a carbonate compound, such as a polyol with a dialkyl carbonate or a polyol with a diaryl carbonate.
[0052] The polyol used in the polycarbonate polyol may be a low molecular weight polyol used in the polyester polyol. On the other hand, the dialkyl carbonate may be dimethyl carbonate or diethyl carbonate, and the diaryl carbonate may be diphenyl carbonate.
[0053] The number average molecular weight of the polymer polyol preferably used in the present invention is preferably 500 or more and 5,000 or less. By making the number average molecular weight of the polymer polyol 500 or more, more preferably 1,500 or more, it is possible to easily prevent the texture of the artificial leather from becoming hard. In addition, by making the number average molecular weight 5,000 or less, more preferably 4,000 or less, it is possible to easily maintain the strength of the polyurethane having a hydrophilic group as a binder.
[0054] (1-2) Organic diisocyanates The organic diisocyanates preferably used in the synthesis of the polyurethane include aromatic diisocyanates having a carbon number of 6 to 20 (excluding carbons in NCO groups, the same applies below), aliphatic diisocyanates having a carbon number of 2 to 18, alicyclic diisocyanates having a carbon number of 4 to 15, araliphatic diisocyanates having a carbon number of 8 to 15, modified products of these diisocyanates (carbodiimide modified products, urethane modified products, urethodione modified products, etc.), and mixtures of two or more of these.
[0055] Specific examples of the aromatic diisocyanate having 6 or more and 20 or less carbon atoms include 1,3- and / or 1,4-phenylene diisocyanate, 2,4- and / or 2,6-tolylene diisocyanate, 2,4'- and / or 4,4'-diphenylmethane diisocyanate (hereinafter abbreviated as MDI), 4,4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatodiphenylmethane, and 1,5-naphthylene diisocyanate. Among these, it is preferable to use MDI, which has excellent flexibility when made into a polyurethane having a hydrophilic group.
[0056] Specific examples of the aliphatic diisocyanate having 2 or more and 18 or less carbon atoms include ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, dodecamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2,6-diisocyanatomethyl caproate, bis(2-isocyanatoethyl)carbonate, and 2-isocyanatoethyl-2,6-diisocyanatohexaate.
[0057] Specific examples of the alicyclic diisocyanate having 4 or more and 15 or less carbon atoms include isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexylene-1,2-dicarboxylate, and 2,5- and / or 2,6-norbornane diisocyanate. Among these, it is preferable to use dicyclohexylmethane-4,4'-diisocyanate, which has excellent durability when made into a polyurethane having a hydrophilic group.
[0058] Specific examples of the aromatic aliphatic diisocyanate having 8 to 15 carbon atoms include m- and / or p-xylylene diisocyanate, and α,α,α',α'-tetramethylxylylene diisocyanate.
[0059] (1-3) Compounds containing active hydrogen components with hydrophilic groups The active hydrogen component-containing compound having a hydrophilic group that is preferably used in the synthesis of the polyurethane includes a compound containing a nonionic group and / or an anionic group and / or a cationic group and active hydrogen. These active hydrogen component-containing compounds can also be used in the form of a salt neutralized with a neutralizing agent. By using this active hydrogen component-containing compound having a hydrophilic group, the stability of the aqueous dispersion used in the manufacturing method of artificial leather can be improved.
[0060] Examples of compounds having a nonionic group and active hydrogen include compounds containing two or more active hydrogen components or two or more isocyanate groups and having a polyoxyethylene glycol group having a molecular weight of 250 to 9,000 on the side chain, and triols such as trimethylolpropane and trimethylolbutane.
[0061] Examples of compounds having an anionic group and active hydrogen include carboxyl group-containing compounds such as 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, and 2,2-dimethylolvaleric acid, and derivatives thereof; sulfonic acid group-containing compounds such as 1,3-phenylenediamine-4,6-disulfonic acid and 3-(2,3-dihydroxypropoxy)-1-propanesulfonic acid, and derivatives thereof; and salts of these compounds neutralized with a neutralizing agent.
[0062] Examples of compounds containing a cationic group and active hydrogen include tertiary amino group-containing compounds such as 3-dimethylaminopropanol, N-methyldiethanolamine, and N-propyldiethanolamine, and derivatives thereof.
[0063] (1-4) Chain extender Examples of chain extenders preferably used in the synthesis of the polyurethane include water, low molecular weight diols such as ethylene glycol, propylene glycol, 1,3-butylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, and neopentyl glycol, alicyclic diols such as 1,4-bis(hydroxymethyl)cyclohexane, aromatic diols such as 1,4-bis(hydroxyethyl)benzene, aliphatic diamines such as ethylenediamine, alicyclic diamines such as isophoronediamine, aromatic diamines such as 4,4-diaminodiphenylmethane, aromatic aliphatic diamines such as xylylenediamine, alkanolamines such as ethanolamine, dihydrazides such as hydrazine and adipic acid dihydrazide, and mixtures of two or more of these.
[0064] Of these, preferred chain extenders are water, low molecular weight diols and aromatic diamines, and more preferred are water, ethylene glycol, 1,4-butanediol, 4,4'-diaminodiphenylmethane and mixtures of two or more of these.
[0065] (1-5) Structure of polyurethane precursor As described above, the polyurethane precursor preferably used in the synthesis of the polyurethane is prepared by reacting the polymer polyol, an organic diisocyanate, and an active hydrogen component-containing compound having a hydrophilic group to form a hydrophilic prepolymer, and then adding and reacting a chain extender.
[0066] (1-6) Crosslinking agent As a crosslinking agent preferably used in the synthesis of the polyurethane, one having two or more reactive groups in the molecule that can react with the reactive group introduced into the polyurethane precursor can be used, and specific examples thereof include polyisocyanate-based crosslinking agents such as water-soluble isocyanate compounds and blocked isocyanate compounds, melamine-based crosslinking agents, carbodiimide-based crosslinking agents, etc. The crosslinking agents can be used alone or in combination of two or more.
[0067] The water-soluble isocyanate compound has two or more isocyanate groups in the molecule, and examples of the water-soluble isocyanate compound include the above-mentioned organic polyisocyanate-containing compounds. Commercially available products include the Bayhydur (registered trademark) series and Desmodur (registered trademark) series manufactured by Bayer MaterialScience Co., Ltd.
[0068] A blocked isocyanate compound has two or more blocked isocyanate groups in the molecule. The blocked isocyanate group refers to the organic polyisocyanate compound blocked with a blocking agent such as amines, phenols, imines, mercaptans, pyrazoles, oximes, or active methylenes. Examples of commercially available products include the "Elastron" (registered trademark) series from Daiichi Kogyo Seiyaku Co., Ltd., the "Duranate" (registered trademark) series from Asahi Kasei Corporation, and the "Takenate" (registered trademark) series from Mitsui Chemicals, Inc.
[0069] Examples of oxazoline crosslinking agents include compounds having two or more oxazoline groups (oxazoline skeletons) in the molecule. Commercially available products include the "Epocross" (registered trademark) series manufactured by Nippon Shokubai Co., Ltd.
[0070] Examples of carbodiimide crosslinking agents include compounds having two or more carbodiimide groups in the molecule. Commercially available products include the "Carbodilite" (registered trademark) series manufactured by Nisshinbo Chemical Inc.
[0071] Among these, it is particularly preferable to use a carbodiimide compound, which gives a polyurethane having a hydrophilic group after the reaction, which has excellent durability and flexibility.
[0072] (1-7) Structure of polyurethane having hydrophilic groups The polyurethane having a hydrophilic group is preferably a polyether-based polyurethane containing a component derived from a polyether-based polyol and / or a polycarbonate-based polyurethane containing a component derived from a polycarbonate-based polyol.
[0073] From the viewpoint of flexibility, it is preferable that the polyurethane having a hydrophilic group contains a component derived from a polyether polyol. By containing a component derived from a polyether polyol, the degree of freedom of the ether bond is high, so that the glass transition temperature is low and the cohesive force is weak, so that the water-dispersible polyurethane having excellent flexibility can be obtained.
[0074] On the other hand, from the viewpoint of durability, it is preferable that the polyurethane having a hydrophilic group contains a component derived from a polycarbonate-based polyol. By containing a component derived from a polycarbonate-based polyol in the polyurethane having a hydrophilic group, the polyurethane having a hydrophilic group can be excellent in water resistance, heat resistance, weather resistance, and mechanical properties due to the high cohesive force of the carbonate group.
[0075] The composition of the polyurethane having a hydrophilic group can be appropriately adjusted depending on the required properties, and a polyether-based polyurethane containing a component derived from a polyether-based polyol or a polycarbonate-based polyurethane containing a component derived from a polycarbonate-based polyol may be used alone or in combination.
[0076] As a method for confirming the constituents of the polyurethane having hydrophilic groups (confirming that the polyurethane having hydrophilic groups contains a constituent component derived from polyester polyol, and that the polyurethane having hydrophilic groups further contains a constituent component derived from polycarbonate polyol), the polyester constituting the artificial leather can be dissolved, and the insoluble matter (polyurethane having hydrophilic groups) can be analyzed by infrared spectroscopy (analytical equipment includes "FT / IR 4000 series" manufactured by JASCO Corporation or an infrared spectroscopy analyzer having equivalent performance) and pyrolysis GC / MS analysis (analytical equipment includes "GCMS-QP5050A" manufactured by Shimadzu Corporation or a pyrolysis GC / MS analyzer having equivalent performance). As a solvent capable of dissolving the polyester constituting the artificial leather, m-cresol or hexafluoroisopropanol can be used, but it is preferable to use hexafluoroisopropanol, which can be handled at room temperature.
[0077] In addition, the polyurethane having a hydrophilic group used in the present invention preferably has an N-acylurea bond and / or an isourea bond. The N-acylurea bond and / or the isourea bond is formed by the reaction of the hydrophilic group with a crosslinking agent having a carbodiimide group, and by forming a crosslinked structure in the polyurethane having a hydrophilic group, the durability of the polyurethane having a hydrophilic group can be improved.
[0078] The presence of the above-mentioned N-acylurea group or isourea group in the polyurethane having a hydrophilic group can be analyzed by performing, for example, a mapping process such as time-of-flight secondary ion mass spectrometry (TOF-SIMS analysis) on a cross section of the artificial leather (an analytical instrument may be, for example, the "TOF.SIMS 5" manufactured by ION-TOF or a TOF-SIMS analyzer having equivalent performance) or infrared spectroscopy (an analytical instrument may be, for example, the "FT / IR 4000 series" manufactured by JASCO Corporation or an infrared spectroscopy analyzer having equivalent performance).
[0079] [Artificial leather] First, the artificial leather of the present invention has a content ratio of polyurethane having a hydrophilic group of 15% by mass or more and 25% by mass or less. By making the content ratio 15% by mass or more, preferably 18% by mass or more, the artificial leather has excellent abrasion resistance. On the other hand, by making the content ratio 25% by mass or less, preferably 22% by mass or less, the artificial leather has a soft feel.
[0080] In the present invention, the content of the polyurethane having a hydrophilic group is measured and calculated by the following method. (1) Cut a 5 cm x 5 cm test piece from the artificial leather and measure the mass (M X ) is measured. (2) The test piece is immersed in hexafluoroisopropanol to dissolve the polyester microfibers from the artificial leather. (3) The insoluble component of (2) (polyurethane having hydrophilic groups) is dried in a dryer at 100°C and the mass (MA ) is measured, and then the content (mass %) of polyurethane having a hydrophilic group is calculated by the following formula.
[0081] Content of polyurethane having hydrophilic groups=(M A / M X ) x 100.
[0082] In the present invention, it is important that polyurethane is attached to 10% to 80% of the outermost filaments of the multifilament constituting the woven fabric.
[0083] By having polyurethane adhere to 10% or more, more preferably 15% or more, and even more preferably 20% or more of the outermost filaments of the multifilament, an artificial leather with excellent shape stability is obtained.
[0084] On the other hand, when polyurethane is attached to 80% or less, more preferably 60% or less, and even more preferably 50% or less of the outermost filaments of the multifilament, an artificial leather with excellent flexibility is obtained.
[0085] In the present invention, the ratio of the filaments to which polyurethane is attached among the outermost filaments of the multifilament is measured and calculated by the following method. (1) Scanning electron microscope (SEM) photographs of the cross sections of the artificial leather were taken, and the number of filaments (N M ), and then the number of filaments to which polyurethane is attached (N p ) is calculated, and the percentage of filaments to which polyurethane is attached is calculated using the following formula.
[0086] Percentage of filaments with polyurethane attached (%) = (N p / N M ) x 100 (2) The measurement in (1) is performed on 20 multifilaments, and the average value is the percentage of filaments to which polyurethane is attached.
[0087] The apparent density of the artificial leather of the present invention is 0.30 g / cm 3 More than 0.40g / cm 3 The apparent density of the artificial leather is preferably 0.30 g / cm or less. 3 More preferably, 0.32 g / cm 3 More preferably, 0.34 g / cm 3 By setting the elastic modulus at 0.40 g / cm or more, the artificial leather has excellent abrasion resistance. 3 Less than or equal to 0.38 g / cm 3 By doing as follows, it is possible to obtain artificial leather with a soft feel.
[0088] In the present invention, the apparent density of the artificial leather is calculated by measuring the thickness and mass per unit area of the artificial leather using the methods specified in JIS L 1913:2010 "Testing methods for general nonwoven fabrics" 6.1.1 (thickness, method A) and 6.2 (mass per unit area), and using the following formula.
[0089] Apparent density of artificial leather (g / cm 3 ) = Mass per unit area of artificial leather (g / cm 2 ) / Thickness of artificial leather (cm).
[0090] The artificial leather of the present invention has a bending resistance of 150 mm or less in the longitudinal direction of the sheet, as defined by Method A (45° cantilever method) described in "8.21 Bending resistance" of JIS L 1096:2010 "Fabric testing methods for woven and knitted fabrics". By setting the bending resistance in this range, the artificial leather can have excellent flexibility. By setting the bending resistance to 150 mm or less, more preferably 100 mm or less, the artificial leather can have higher flexibility.
[0091] The artificial leather of the present invention preferably has an abrasion loss of 30 mg or less when abraded 50,000 times in the Martindale abrasion test specified in "8.19.5 E method (Martindale method)" of "8.19 Abrasion resistance and discoloration due to friction" of JIS L 1096:2005 "Testing methods for woven and knitted fabrics". From the viewpoint of suppressing deterioration of the appearance of the artificial leather, the abrasion loss is more preferably 25 mg or less.
[0092] Furthermore, the artificial leather of the present invention preferably has an abrasion loss of 10 mg or less when measured after 10,000 abrasion cycles in a Martindale abrasion test specified in "8.19.5 E method (Martindale method)" of "8.19 Abrasion resistance and friction discoloration" of "Testing methods for woven and knitted fabrics" in JIS L 1096:2005 after xenon irradiation specified in "7.2 Exposure method a) First exposure method" of JIS L 0843:2006 "Testing methods for color fastness to xenon arc lamp light". By having an abrasion loss of 10 mg or less after xenon irradiation, the artificial leather has durability that allows it to be used for a long period of time in areas exposed to sunlight, such as automobile seats.
[0093] [Manufacturing method of artificial leather] The method for producing an artificial leather of the present invention is a method for producing an artificial leather comprising the following steps (1) to (3) in this order. (1) A process of entangling and integrating a nonwoven fabric made of ultrafine fiber-developing fibers with a woven fabric to form a fibrous base material. (2) A process for obtaining a shrunk sheet having a width of 0.85L or more and 0.95L or less, where L is the width of the sheet obtained by impregnating the fibrous base material with an aqueous dispersion of polyurethane having a hydrophilic group and then coagulating the polyurethane. (3) A step of producing polyester ultrafine fibers from the ultrafine fiber-producing fibers of the shrink sheet.
[0094] The details are explained below.
[0095] <Step of forming fibrous base material> In this process, a nonwoven fabric made of ultrafine fiber development type fibers and a woven fabric are subjected to an entanglement treatment to form a fibrous base material.
[0096] As the ultrafine fiber-producing fiber, it is preferable to use islands-in-sea type composite fibers in which two thermoplastic resin components with different solvent solubility (two or three components when the island fiber is a core-sheath composite fiber) are used as a sea component and an island component, and the sea component is dissolved and removed using a solvent or the like to convert the island components into ultrafine fibers, because appropriate gaps can be imparted between the island components, i.e., between the ultrafine fibers inside the fiber bundle, when the sea component is removed. This is because this can provide appropriate gaps between the island components, i.e., between the ultrafine fibers inside the fiber bundle, from the viewpoint of the texture and surface quality of the artificial leather.
[0097] For islands-in-sea type composite fibers, a method using a polymer mutual alignment body in which two components, a sea component and an island component (three components when the island fiber is a core-sheath composite fiber), are mutually aligned and spun using an islands-in-sea type composite spinneret is preferred from the viewpoint of obtaining ultrafine fibers with a uniform single fiber diameter.
[0098] As the sea component of the islands-in-sea type composite fiber, polyethylene, polypropylene, polystyrene, copolymer polyesters copolymerized with sodium sulfoisophthalic acid or polyethylene glycol, and polylactic acid can be used, but from the viewpoints of spinnability, ease of elution, etc., polystyrene and copolymer polyesters are preferably used.
[0099] The mass ratio of the sea component to the island components in the islands-in-sea type composite fiber preferably used in the present invention is preferably in the range of sea component:island component=10:90 to 80:20. When the mass ratio of the sea component is 10% by mass or more, the island components are easily and sufficiently ultrafine. When the mass ratio of the sea component is 80% by mass or less, the proportion of eluted components is small, thereby improving productivity. The mass ratio of the sea component to the island components is more preferably in the range of sea component:island component=20:80 to 70:30.
[0100] As described above, either a short fiber nonwoven fabric or a long fiber nonwoven fabric can be used as the nonwoven fabric constituting the fibrous base material. However, a short fiber nonwoven fabric is preferred because it has more fibers oriented in the thickness direction of the artificial leather than a long fiber nonwoven fabric, and therefore it is possible to obtain a highly dense feel on the surface of the artificial leather when it is raised.
[0101] When a staple fiber nonwoven fabric is used as the fibrous substrate, the obtained ultrafine fiber developing type fiber is preferably subjected to a crimping process and cut to a predetermined length to obtain raw cotton. The crimping process and the cutting process can be carried out by a known method.
[0102] Next, the obtained raw cotton is made into a fiber web by a cross wrapper or the like. The obtained fiber web is then entangled to obtain a nonwoven fabric. As a method for entangling the fiber web to obtain a nonwoven fabric, a needle punching process, a water jet punching process, or the like can be used, but the needle punching process, which has a high entanglement efficiency, is preferred.
[0103] The nonwoven fabric and the woven fabric are then laminated and entangled together. The nonwoven fabric and the woven fabric can be entangled together by laminating the woven fabric on one or both sides of the nonwoven fabric, or by sandwiching the woven fabric between a plurality of nonwoven fabric webs and then entangling the fibers of the nonwoven fabric and the woven fabric by needle punching, water jet punching, or the like. From the viewpoint of production efficiency, it is preferable to laminate the woven fabric on both sides of the nonwoven fabric and then perform needle punching.
[0104] The apparent density of the nonwoven fabric made of the composite fiber (ultrafine fiber development type fiber) after the entanglement treatment and the fibrous base material made of the woven fabric is 0.20 g / cm 3 More than 0.30g / cm 3 It is preferable that the apparent density is 0.20 g / cm or less. 3 More preferably, 0.23 g / cm 3 By setting the apparent density at 0.30 g / cm or more, the fibrous base material can obtain sufficient shape stability and dimensional stability. 3 Less than or equal to 0.28 g / cm 3By setting the above ratio, it is possible to maintain a sufficient space for applying the polyurethane having a hydrophilic group.
[0105] The fibrous base material can be subjected to a heat shrinkage treatment using warm water or steam in order to improve the denseness of the fibers. However, in the present invention, since the sheet is shrunk after being impregnated with the aqueous dispersion containing the polyurethane precursor, it is preferable not to carry out a shrinkage treatment before being impregnated with the aqueous dispersion containing the polyurethane precursor.
[0106] <Step of forming an impregnated sheet and shrinking it in the width direction> In this process, the fibrous base material is impregnated with an aqueous dispersion containing a polyurethane precursor, and then a heat drying process is performed to form an impregnated sheet containing the fibrous base material and a polyurethane having a hydrophilic group as components. When the width of the fibrous base material before the sheet is impregnated is L, a shrunken sheet is obtained having a width of 0.85L to 0.95L.
[0107] In the method for producing the artificial leather of the present invention, the coagulation after the application of the aqueous dispersion can be performed by a coagulation method commonly used in the field, such as a dry heat coagulation method or a liquid coagulation method. When the dry heat coagulation method is used, it is preferable to apply the aqueous dispersion to the fibrous substrate, heat treat the substrate at a temperature of 120°C to 180°C, and perform dry heat coagulation to provide the fibrous substrate with a polyurethane having a hydrophilic group. In addition, as the liquid coagulation, an acid coagulation method in which a coagulation treatment is performed using a coagulation solvent having a pH of 1 to 3, or a hot water coagulation method in which a coagulation treatment is performed using hot water having a pH of 80°C to 100°C can be used.
[0108] The concentration of the polyurethane precursor in the aqueous dispersion (content of the polyurethane precursor in 100% by mass of the aqueous dispersion) is preferably 3% by mass or more and 30% by mass or less. By making it 3% by mass or more, more preferably 5% by mass or more, the polyurethane precursor can be uniformly applied to the fibrous substrate even when the amount of the polyurethane precursor applied is small. On the other hand, by making it 30% by mass or less, more preferably 15% by mass or less, the storage stability of the aqueous dispersion can be improved.
[0109] When the dry heat coagulation method is used as the coagulation method, it is preferable to adjust the coagulation temperature to 55°C or more and 80°C or less. By setting the coagulation temperature to 55°C or more, more preferably 60°C or more, gelation during preparation and storage of the aqueous dispersion can be suppressed. On the other hand, by setting the temperature to 80°C or less, more preferably 70°C or less, coagulation of the polyurethane precursor proceeds before water evaporates from the fibrous base material, and a structure similar to that obtained by wet coagulation of a solvent-based polyurethane, that is, a structure in which the polyurethane does not strongly bind the fibers constituting the nonwoven fabric or woven fabric, can be formed, thereby achieving good flexibility and resilience.
[0110] In the method for producing the artificial leather of the present invention, when the dry heat coagulation method is used, an inorganic salt can be contained in the aqueous dispersion. By containing an inorganic salt, the aqueous dispersion can be given heat-sensitive coagulation properties. In the present invention, the heat-sensitive coagulation property refers to the property that when the aqueous dispersion is heated and reaches a certain temperature (coagulation temperature), the fluidity of the aqueous dispersion decreases and the aqueous dispersion coagulates.
[0111] In the present invention, when an inorganic salt is used as a heat-sensitive coagulant, it is preferable to use a monovalent cation-containing inorganic salt. The monovalent cation-containing inorganic salt is preferably sodium chloride and / or sodium sulfate. A monovalent cation-containing inorganic salt with a small ionic valence has little effect on the stability of the aqueous dispersion, and by adjusting the amount of the monovalent cation-containing inorganic salt added, the heat-sensitive coagulation temperature can be strictly controlled while ensuring the stability of the aqueous dispersion.
[0112] Further, in the present invention, the content of the monovalent cation-containing inorganic salt in the aqueous dispersion is preferably 10% by mass or more and 50% by mass or less with respect to the polyurethane precursor. By making the content 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, the ions present in a large amount in the aqueous dispersion act uniformly on the polyurethane precursor particles, so that the coagulation can be completed quickly at a specific heat-sensitive coagulation temperature. This makes it possible to obtain a more remarkable effect in proceeding with the coagulation of the polyurethane precursor in a state in which a large amount of water is contained in the fibrous base material as described above. As a result, it is possible to form a structure very similar to that obtained by wet coagulation of a solvent-based polyurethane, and to achieve good flexibility and resilience. Furthermore, by making the amount added as described above, the inorganic salt acts as an inhibitor in the fusion of the polyurethane precursor particles, and it is also possible to suppress the hardening of the polyurethane precursor due to the formation of a continuous film. On the other hand, by making the content 50% by mass or less, it is possible to leave a moderate continuous film structure of the polyurethane precursor and suppress the deterioration of the physical properties. It is also possible to maintain the stability of the aqueous dispersion.
[0113] In the method for producing the artificial leather of the present invention, it is also preferable to add a crosslinking agent to the aqueous dispersion. The crosslinking agent introduces a three-dimensional network structure into the polyurethane precursor, thereby improving physical properties such as abrasion resistance.
[0114] The concentration of the crosslinking agent in the aqueous dispersion is preferably 1% by mass or more and 10% by mass or less relative to the mass of the polyurethane precursor. By making the concentration of the crosslinking agent in the aqueous dispersion 1% by mass or more, more preferably 2% by mass or more, the crosslinking agent can introduce a larger amount of three-dimensional network structure into the polyurethane precursor, and an artificial leather with excellent abrasion resistance and the like can be obtained. On the other hand, by making the concentration 10% by mass or less, more preferably 7% by mass or less, it is possible to prevent the excessive crosslinking agent from inhibiting the coagulation of the polyurethane precursor when the polyurethane precursor is formed, and it is easy to prevent the deterioration of physical properties such as abrasion resistance.
[0115] The crosslinking agent preferably used in the method for producing the artificial leather of the present invention is preferably a carbodiimide crosslinking agent and / or a blocked isocyanate crosslinking agent. In this way, a three-dimensional crosslinking structure can be imparted to the molecules of the polymeric elastomer in the artificial leather by N-acylurea bonds and / or isourea bonds, which have excellent physical properties such as light resistance, heat resistance, and abrasion resistance, and flexibility, and the artificial leather can be dramatically improved in physical properties such as durability and abrasion resistance while maintaining its flexibility.
[0116] After impregnating and solidifying the aqueous dispersion, a shrunken sheet is obtained with a width of 0.85L to 0.95L, where L is the width of the fibrous substrate before the sheet is impregnated. Methods for shrinking the sheet in the width direction include dry heat treatment at a temperature of 100°C to 180°C and hot water treatment with hot water at 80°C to 100°C. Dry heat treatment includes treatment in which hot air is applied to one or both sides of the sheet using a floater dryer, drum dryer, pin tenter dryer, etc., and hot water treatment includes treatment in which the sheet is immersed in hot water at 80°C to 100°C, squeezed with a mangle, and then dried in a dryer.
[0117] From the viewpoint of production efficiency, it is preferable that the coagulation method and the shrinkage method of the aqueous dispersion are the same.
[0118] Shrinking the sheet in the width direction can increase the density of the artificial leather surface. In particular, shrinking the sheet in the width direction after impregnation and solidification of an aqueous polyurethane dispersion can prevent the polyurethane from strongly adhering to the woven fabric, and can soften the texture of the artificial leather.
[0119] The degree of shrinkage in the width direction of the sheet can be adjusted by the heat treatment temperature and heat treatment time, and the above-mentioned effect can be made sufficient by making the shrinkage 5% or more, more preferably 10% or more, of the width of the fibrous base material before impregnation.
[0120] On the other hand, by making the width 15% or less of the width of the fibrous base material before impregnation, quality defects such as wrinkling of the sheet can be prevented.
[0121] When dry heat treatment is used as the shrinkage treatment, the shrinkage of the sheet can be increased by setting the temperature of the dry heat treatment to 100° C. or higher, preferably 120° C. or higher, and more preferably 130° C. or higher. On the other hand, by setting the temperature of the dry heat treatment to 180° C. or lower, and preferably 160° C. or lower, the deterioration of the durability of the artificial leather due to the decomposition of the polyurethane can be suppressed.
[0122] When dry heat treatment is used as the shrinkage treatment, the dry heat treatment time is preferably 5 minutes or more and 30 minutes or less. Heating for 5 minutes or more, more preferably 10 minutes or more, can increase the shrinkage of the sheet. Dry heat treatment time of 30 minutes or less, preferably 25 minutes or less, can suppress deterioration of the durability of the artificial leather due to decomposition of polyurethane.
[0123] <Process for producing polyester ultrafine fibers> In this process, polyester ultrafine fibers are expressed from the ultrafine fiber-expressing fibers of the shrink sheet, and a sheet is formed containing, as components, a fibrous base material composed of polyester ultrafine fibers and woven fabric, and polyurethane having hydrophilic groups.
[0124] When islands-in-sea type composite fibers are used as the ultrafine fiber-producing fibers, the ultrafine fiber processing (sea-component removal processing) can be carried out, for example, by immersing the islands-in-sea type composite fibers in a solvent and then carrying out a heat treatment. The solvent for dissolving the sea component can be appropriately selected depending on the type of the sea component, and when the sea component is a copolymer polyester, an alkaline aqueous solution such as sodium hydroxide can be used, but it is preferable to carry out the alkaline processing using an alkaline aqueous solution, which is expected to have the effect of reducing the adhesion between the woven fabric and the polyurethane.
[0125] When an aqueous alkaline solution is used as a solvent for the sea-removal treatment, the molar concentration of the aqueous alkaline solution is preferably 3 mol / L or less in order to prevent excessive deterioration of the polyurethane having a hydrophilic group.
[0126] <Finishing process> In the method for producing the artificial leather of the present invention, it is preferable to carry out various finishing steps, as in the case of general artificial leathers.
[0127] First, the method for producing an artificial leather of the present invention preferably includes a dyeing step for dyeing the artificial leather. As the dyeing process, various methods commonly used in the field can be adopted, such as a flow dyeing process using a jigger dyeing machine or a flow dyeing machine, a dip dyeing process such as a thermosol dyeing process using a continuous dyeing machine, or a printing process on the napped surface by roller printing, screen printing, inkjet printing, sublimation printing, vacuum sublimation printing, etc. Among them, it is preferable to use a flow dyeing machine, since it is possible to soften the unbrushed artificial leather or artificial leather by giving a kneading effect at the same time as dyeing the unbrushed artificial leather or artificial leather. In addition, various resin finishing processes can be applied after dyeing, if necessary.
[0128] In addition, finishing treatment may be carried out using, for example, a softener such as silicone, an antistatic agent, a water repellent, a flame retardant, a light fastener, an antibacterial agent, etc. in the same bath as dyeing or after dyeing.
[0129] In the present invention, from the viewpoint of production efficiency, it is also a preferred embodiment to cut the film in half in the thickness direction, regardless of whether it is before or after the dyeing step.
[0130] In the method for producing the artificial leather of the present invention, it is also preferable to include a nap raising step, regardless of whether it is before or after the dyeing step. The method for forming nap is not particularly limited, and various methods commonly used in the field, such as buffing with sandpaper, can be used.
[0131] When the artificial leather is to be subjected to a nap raising treatment, a lubricant such as a silicone emulsion can be applied to the surface of the artificial leather before the nap raising treatment. Also, by applying an antistatic agent before the nap raising treatment, grinding powder generated from the artificial leather by grinding is less likely to accumulate on the sandpaper. In this way, the artificial leather is formed.
[0132] Furthermore, in the method for producing an artificial leather of the present invention, the artificial leather can be subjected to post-processing such as hole-making such as perforation, embossing, laser processing, Pinsonic processing, and printing, if necessary.
[0133] [Uses include vehicle interior materials, vehicle parts, seats, etc.] The artificial leather obtained by the present invention can be suitably used as an interior material having a very elegant appearance as a surface material for furniture, chairs, and wall materials, and for seats, ceilings, and interiors in vehicle cabins such as automobiles, trains, and aircraft; uppers and trims of shoes such as shirts, jackets, casual shoes, sports shoes, men's shoes, and women's shoes; bags, belts, wallets, and the like; and industrial materials used in parts of these materials, such as wiping cloths, polishing cloths, and CD curtains.
[0134] For example, automobile interior materials containing the artificial leather are preferred because they can utilize the characteristics of high strength, excellent flexibility, and excellent abrasion resistance. Such automobile interior materials are preferably used for automobile parts such as steering wheels, horn switches, shift knobs, dashboards, instrument panels, glove boxes, floor carpets, floor mats, ceiling linings, sun visors, and assist grips, and it is more preferred that at least a part of these automobile parts is the artificial leather. Note that the "automobile" in the present invention is not limited to so-called general passenger cars, but also includes some industrial machines, construction machines, and agricultural machines that can carry humans or animals, such as excavators, crane trucks, tractors, and combines.
[0135] Similarly, seats containing the artificial leather are also preferred because they can take advantage of the characteristics of high strength, excellent flexibility, and excellent wear resistance. For such seats, it is more preferable that at least a part of the covering material of the headrest, seat surface, armrest, footrest, etc., for example, the part that comes into direct contact with the seated person, is made of the artificial leather. Of course, the seat of the present invention can be used not only for vehicles such as automobiles, aircraft, railway vehicles, and ships, but also for homes, offices, and stores. The "seat" referred to in the present invention also includes chairs, benches, sofas, couches, stools, and chairs. EXAMPLES
[0136] The artificial leather of the present invention will be described more specifically with reference to examples, but the present invention is not limited to these examples.
[0137] [Evaluation method] The evaluation methods and measurement conditions used in the examples are described below. Unless otherwise specified, the measurements of each physical property were performed according to the above-mentioned methods.
[0138] (1) Average single fiber diameter (μm): The average single fiber diameter (μm) was measured and calculated by the above-mentioned method using a scanning electron microscope (SEM) "VHX-D500 / D510" manufactured by Keyence Corporation.
[0139] (2) Content of polyurethane having hydrophilic groups (mass%): The content (mass %) of the polyurethane having a hydrophilic group was measured and calculated by the above-mentioned method.
[0140] (3) The percentage of filaments with polyurethane attached to the outermost filaments of the multifilament (%): The percentage (%) of the filaments to which polyurethane was attached among the outermost filaments of the multifilament was measured and calculated by the above-mentioned method.
[0141] (4) Bending resistance of artificial leather: Based on Method A (45° cantilever method) described in 8.21.1 of "Bending resistance" in JIS L 1096:2010 "Testing methods for woven and knitted fabrics," five test pieces measuring 2 cm x 30 cm were prepared in the longitudinal direction of the sheet and placed on a horizontal table with a 45° inclined surface. The test pieces were slid and the scale was read when the center point of one end of the test piece came into contact with the inclined surface, and the average value of the five pieces was calculated.
[0142] (5) Abrasion loss of artificial leather (mg): When measuring and calculating the abrasion weight loss (mg) of the artificial leather, a Martindale abrasion tester "Model 406" manufactured by James H. Heal & Co. was used as the abrasion tester, and the standard abrasion cloth was "ABRASTIVE CLOTH SM25" manufactured by the same company. A load of 12 kPa was applied to the artificial leather, and measurements were taken after 50,000 abrasion cycles. The abrasion weight loss was calculated using the mass of the artificial leather before and after abrasion according to the following formula.
[0143] Abrasion loss (mg) = mass before abrasion (mg) - mass after abrasion (mg) The wear loss (mg) was calculated by rounding off the value to the first decimal place.
[0144] (6) Abrasion loss (mg) of artificial leather after xenon irradiation: For the measurement and calculation of the abrasion loss (mg) of the artificial leather after xenon irradiation, irradiation was performed as specified in "7.2 Exposure method a) First exposure method" of JIS L 0843:2006 "Test method for color fastness to xenon arc lamp light", and then a Martindale abrasion tester "Model 406" manufactured by James H. Heal & Co. and a standard abrasion cloth "ABRASTIVE CLOTH SM25" manufactured by the same company were used. A load of 12 kPa was applied to the artificial leather, and measurements were performed after 10,000 abrasion cycles. The abrasion loss was calculated using the mass of the artificial leather before and after abrasion according to the following formula.
[0145] Abrasion loss (mg) = mass before abrasion (mg) - mass after abrasion (mg) The wear loss (mg) was calculated by rounding off the value to the first decimal place.
[0146] [Polyurethane precursor] The polyurethane precursors used in the examples and comparative examples are as follows.
[0147] PU-A (polyether-based polyurethane precursor containing components derived from polyether-based polyol): A polyurethane precursor consisting of polytetramethylene glycol as a polymeric polyol, MDI as an organic diisocyanate, 2,2-dimethylolpropionic acid as an active hydrogen component-containing compound having a hydrophilic group, and ethylene glycol as a chain extender.
[0148] PU-B (polycarbonate-based polyurethane precursor containing components derived from polycarbonate-based polyol): A polyurethane precursor consisting of polyhexamethylene carbonate diol as a polymeric polyol, MDI as an organic diisocyanate, 2,2-dimethylolpropionic acid as an active hydrogen component-containing compound having a hydrophilic group, and ethylene glycol as a chain extender.
[0149] [fabric] The woven fabrics used in the examples and comparative examples are as follows.
[0150] Fabric A: A plain weave fabric (weight 75 g / m) with a warp density of 95 threads / 2.54 cm and 76 threads / 2.54 cm, made of a multifilament consisting of 72 filaments with an average single fiber diameter of 11 μm made of polyethylene terephthalate with an intrinsic viscosity of 0.65 and twisted at 2,500 T / m for both the weft and warp. 2 ).
[0151] Fabric B: A plain weave fabric (weight 75 g / m) with a warp density of 95 threads / 2.54 cm and 76 threads / 2.54 cm, made of a multifilament consisting of 40 filaments with an average single fiber diameter of 15 μm made of polyethylene terephthalate with an intrinsic viscosity of 0.65, twisted at 2,500 T / m for both the weft and warp. 2).
[0152] Fabric C: A plain weave fabric (weight 75 g / m) with a warp density of 190 threads / 2.54 cm and 152 threads / 2.54 cm, made of a multifilament consisting of 68 filaments with an average single fiber diameter of 8 μm made of polyethylene terephthalate with an intrinsic viscosity of 0.65 and twisted at 2,500 T / m for both the weft and warp. 2 ).
[0153] [Example 1] <Step of forming fibrous base material> A polyester copolymerized with 8 mol% of sodium 5-sulfoisophthalate was used as the sea component, and a polyethylene terephthalate with an intrinsic viscosity of 0.73 was used as the island component. The mixture was melt spun using an islands-in-sea composite spinneret with 16 islands / hole under the conditions of a spinning temperature of 285°C, an islands / sea mass ratio of 80 / 20, a throughput of 1.6 g / min / hole, and a spinning speed of 1,100 m / min. The mixture was then stretched 3.7 times in an oil bath and cut to a length of 51 mm to obtain raw cotton for islands-in-sea composite fibers with a single fiber fineness of 3.8 dtex. The raw cotton for the islands-in-sea composite fibers was then passed through carding and cross-wrapping processes to produce an apparent density of 0.09 g / cm. 3 After forming the laminated web, fabric A was laminated and the number of threads / cm was 3,500. 2 The fabric was needle punched at a punch density of 690g / m 2 The thickness is 3.0 mm, the width is 170 cm, and the apparent density is 0.23 g / cm 3 Thus, a fibrous base material consisting of a nonwoven fabric made of the sea-island composite fibers and a woven fabric was obtained.
[0154] <Step of forming an impregnated sheet and shrinking it in the width direction> As the polyurethane precursor, an aqueous dispersion was prepared containing 12 parts by mass of PU-A, a polyether polyurethane precursor, 1 part by mass of a carbodiimide crosslinking agent ("Carbodilite" (registered trademark) V-02-L2 manufactured by Nisshinbo Chemical Inc.), 5 parts by mass of sodium sulfate, and 82 parts by mass of water. After impregnating the fibrous base material, the aqueous dispersion was squeezed with a mangle so that the pickup rate of the aqueous dispersion was 200% by mass of the fibrous base material, and the polyurethane precursor was solidified by heating for 10 minutes with hot air at 100°C, and then heated for 10 minutes with hot air at 150°C. The sheet was shrunk in the width direction by 12% compared to the width L of the fibrous base material before impregnation, and an impregnated sheet having a width of 150 cm (0.88 L) and consisting of a nonwoven fabric of islands-in-the-sea composite fiber, a woven fabric, and a polyurethane having a hydrophilic group was obtained.
[0155] <Process for producing polyester ultrafine fibers> The obtained impregnated sheet was immersed in a 5% aqueous sodium hydroxide solution, and then squeezed with a mangle so that the pick-up rate of the aqueous sodium hydroxide solution was 100%, and then heat-treated with steam at 95°C for 10 minutes to alkali-decompose the sea component of the islands-in-sea type composite fibers. Next, the excess sodium hydroxide was washed away with water, and a sheet composed of polyester ultrafine fibers, woven fabric, and polyurethane having hydrophilic groups was obtained.
[0156] <Finishing process> The obtained sheet was cut in half perpendicular to the thickness direction, and the cut surface was ground with endless sandpaper having a grit size of 180 to obtain a napped sheet having a thickness of 0.9 mm.
[0157] The resulting napped sheet was dyed with a disperse dye at a temperature of 120°C using a jet dyeing machine. It was then dried in a dryer to obtain an artificial leather containing 23% by mass of polyurethane having a hydrophilic group and an average single fiber diameter of ultrafine fibers of 4.4 μm. The proportion (%) of filaments to which polyurethane was attached among the outermost filaments of the multifilaments constituting the woven fabric of the resulting artificial leather was 30%, and the artificial leather had a soft texture and excellent durability. The results are shown in Table 1.
[0158] [Example 2] An artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23 mass % of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1, except that in the <step of forming a fibrous base material>, the woven fabric was changed to woven fabric B. The width of the impregnated sheet obtained in the <step of forming an impregnated sheet and shrinking it in the width direction> was shrunk by 12% in the width direction compared to the width L of the fibrous base material before impregnation, to 150 cm (0.88 L).
[0159] The ratio (%) of filaments to which polyurethane was attached among the outermost filaments of the multifilament constituting the obtained artificial leather fabric was 45%, and although the artificial leather was slightly inferior in flexibility compared to Example 1, it had a soft feel and excellent durability. The results are shown in Table 1.
[0160] [Example 3] An artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23 mass % of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1, except that in the <step of forming a fibrous base material>, the woven fabric was changed to woven fabric C. The width of the impregnated sheet obtained in the <step of forming an impregnated sheet and shrinking it in the width direction> was shrunk by 12% in the width direction compared to the width L of the fibrous base material before impregnation, to 150 cm (0.88 L).
[0161] The ratio (%) of filaments to which polyurethane was attached among the outermost filaments of the multifilament constituting the obtained artificial leather fabric was 65%, and although the artificial leather was slightly inferior in flexibility compared to Example 1, it had a soft feel and excellent durability. The results are shown in Table 1.
[0162] [Example 4] An artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23 mass % of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1, except that in the <step of forming an impregnated sheet and shrinking it in the width direction>, the heating conditions after solidifying the polyurethane precursor were changed to 10 minutes with hot air at 120° C. The width of the impregnated sheet obtained in the <step of forming an impregnated sheet and shrinking it in the width direction> was shrunk by 6% in the width direction compared to the width L of the fibrous base material before impregnation, to 160 cm (0.94 L).
[0163] The ratio (%) of filaments to which polyurethane was attached among the outermost filaments of the multifilament constituting the obtained artificial leather fabric was 39%, and although the artificial leather was slightly inferior in flexibility to that of Example 1, it had a soft feel and excellent durability. The results are shown in Table 1.
[0164] [Example 5] An artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23 mass % of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1, except that in the <step of forming an impregnated sheet and shrinking it in the width direction>, the polyurethane precursor was changed to PU-B, which is a polycarbonate-based polyurethane precursor. The width of the impregnated sheet obtained in the <step of forming an impregnated sheet and shrinking it in the width direction> was 150 cm (0.88 L), which was shrunk by 12% in the width direction compared to the width L of the fibrous base material before impregnation.
[0165] The ratio (%) of filaments to which polyurethane was attached among the outermost filaments of the multifilament constituting the obtained artificial leather fabric was 32%, and although the artificial leather was slightly inferior in flexibility compared to Example 1, it had a soft feel and extremely excellent durability. The results are shown in Table 1.
[0166] [Example 6] An artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 18 mass % of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1, except that in the <step of forming an impregnated sheet and shrinking it in the width direction>, the pickup rate of the aqueous dispersion was set to 140% by mass of the fibrous substrate. The width of the impregnated sheet obtained in the <step of forming an impregnated sheet and shrinking it in the width direction> was 150 cm (0.88 L), which was shrunk by 12% in the width direction compared to the width L of the fibrous substrate before impregnation.
[0167] The percentage (%) of the filaments to which polyurethane was attached among the outermost filaments of the multifilament constituting the artificial leather fabric obtained was 22%, and the artificial leather had a soft feel and excellent durability. The results are shown in Table 1.
[0168] [Example 7] An artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23 mass % of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1, except that in the <step of forming an impregnated sheet and shrinking it in the width direction>, the coagulation of the polyurethane precursor and the heating conditions after coagulation were changed to steam at 98° C. The width of the impregnated sheet obtained in the <step of forming an impregnated sheet and shrinking it in the width direction> was shrunk by 5% in the width direction compared to the width L of the fibrous base material before impregnation, to 162 cm (0.95 L).
[0169] The ratio (%) of filaments to which polyurethane was attached among the outermost filaments of the multifilament constituting the obtained artificial leather fabric was 47%, and although the artificial leather was slightly inferior in flexibility compared to Example 1, it had a soft feel and excellent durability. The results are shown in Table 1.
[0170] [Example 8] An artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23 mass % of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1, except that in the <step of developing polyester ultrafine fibers>, the concentration of sodium hydroxide was changed to 3% and the pickup rate was changed to 200%. The width of the impregnated sheet obtained in the <step of forming an impregnated sheet and shrinking it in the width direction> was shrunk by 12% in the width direction compared to the width L of the fibrous base material before impregnation, to 150 cm (0.88 L).
[0171] The ratio (%) of filaments to which polyurethane was attached among the outermost filaments of the multifilament constituting the obtained artificial leather fabric was 40%, and although the artificial leather was slightly inferior in flexibility compared to Example 1, it had a soft feel and extremely excellent durability. The results are shown in Table 1.
[0172] [Comparative Example 1] An artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 23 mass % of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1, except that in <step of forming an impregnated sheet and shrinking it in the width direction>, the fibrous base material was shrunk in the width direction to 150 cm with hot water at 97° C. before impregnating with the aqueous dispersion, and shrinkage in the width direction was not performed after solidification of the polyurethane precursor. Note that the width of the impregnated sheet obtained in <step of forming an impregnated sheet and shrinking it in the width direction> was not shrunk in the width direction compared to the width L of the fibrous base material before impregnation, and remained at 150 cm (1.00 L).
[0173] The ratio (%) of fibers to which polyurethane was attached among the outermost filaments of the multifilament constituting the filament of the obtained artificial leather was 95%, and the obtained artificial leather had excellent durability, but the texture was hard. The results are shown in Table 1.
[0174] [Comparative Example 2] An artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 13 mass % of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1, except that in the <step of forming an impregnated sheet and shrinking it in the width direction>, the pickup rate of the aqueous dispersion was set to 100% by mass of the fibrous substrate. The width of the impregnated sheet obtained in the <step of forming an impregnated sheet and shrinking it in the width direction> was 150 cm (0.88 L), which was shrunk by 12% in the width direction compared to the width L of the fibrous substrate before impregnation.
[0175] The ratio (%) of filaments to which polyurethane was attached among the outermost filaments of the multifilament constituting the artificial leather fabric obtained was 8%, and the artificial leather obtained had an excellent feel, but was significantly inferior in durability. The results are shown in Table 1.
[0176] [Comparative Example 3] An artificial leather having an average single fiber diameter of ultrafine fibers of 4.4 μm and containing 29 mass % of polyurethane having a hydrophilic group was obtained in the same manner as in Example 1, except that in the <step of forming an impregnated sheet and shrinking it in the width direction>, the pickup rate of the aqueous dispersion was set to 250% by mass of the fibrous substrate. The width of the impregnated sheet obtained in the <step of forming an impregnated sheet and shrinking it in the width direction> was 150 cm (0.88 L), which was shrunk by 12% in the width direction compared to the width L of the fibrous substrate before impregnation.
[0177] The ratio (%) of filaments to which polyurethane was attached among the outermost filaments of the multifilament composing the artificial leather fabric obtained was 82%, and the artificial leather obtained had excellent durability, but had a hard feel. The results are shown in Table 1.
[0178] [Comparative Example 4] In the <step of forming an impregnated sheet and shrinking it in the width direction>, before impregnating the fibrous substrate with the aqueous dispersion, the fibrous substrate was shrunk in the width direction to 150 cm with hot water at 97°C and polyvinyl alcohol with a saponification degree of 98% was added at 10 mass% relative to the mass of the fibrous substrate, to obtain an artificial leather containing ultrafine fibers with an average single fiber diameter of 4.4 μm and 23 mass% of polyurethane having a hydrophilic group. The width of the impregnated sheet obtained in the <step of forming an impregnated sheet and shrinking it in the width direction> was not shrunk in the width direction relative to the width L of the fibrous substrate before impregnation and remained at 150 cm (1.00 L).
[0179] The ratio (%) of fibers to which polyurethane was attached among the outermost filaments of the multifilament constituting the filament of the obtained artificial leather was 95%, and the obtained artificial leather had excellent durability, but the texture was hard. The results are shown in Table 1. <Step of forming fibrous base material> In the same manner as in Example 1, a fibrous base material composed of a nonwoven fabric made of sea-island composite fibers and a woven fabric was obtained.
[0180] <Step of forming an impregnated sheet and shrinking it in the width direction> Before impregnating with the aqueous dispersion, the fibrous substrate was shrunk in the width direction to 150 cm using hot water at 97°C, and at the same time, polyvinyl alcohol with a saponification degree of 98% was added in an amount of 10 mass% relative to the mass of the fibrous substrate, and then dried with hot air at 100°C to obtain a fibrous substrate with polyvinyl alcohol. Next, an aqueous dispersion was prepared as a polyurethane precursor, consisting of 12 parts by mass of PU-A, a polyether polyurethane precursor, 1 part by mass of a carbodiimide crosslinking agent ("Carbodilite" (registered trademark) V-02-L2 manufactured by Nisshinbo Chemical Inc.), 5 parts by mass of sodium sulfate, and 82 parts by mass of water. After impregnating a fibrous base material, the aqueous dispersion was squeezed with a mangle so that the pick-up rate of the aqueous dispersion was 200% by mass of the fibrous base material, and the polyurethane precursor was solidified by heating for 10 minutes with hot air at 100°C, and then heated for 10 minutes with hot air at 150°C to obtain an impregnated sheet consisting of a nonwoven fabric of islands-in-the-sea composite fibers, a woven fabric, a polyurethane having a hydrophilic group, and polyvinyl alcohol.
[0181] <Process for producing polyester ultrafine fibers> The obtained impregnated sheet was subjected to an alkali treatment in the same manner as in Example 1 to develop polyester ultrafine fibers, and the polyvinyl alcohol was removed with hot water at 100°C to obtain a sheet composed of polyester ultrafine fibers, woven fabric, and polyurethane having hydrophilic groups.
[0182] <Finishing process> The obtained sheet was subjected to a finishing process in the same manner as in Example 1 to obtain an artificial leather containing ultrafine fibers with an average single fiber diameter of 4.4 μm and 23 mass % of polyurethane having a hydrophilic group. The ratio (%) of filaments to which polyurethane was attached among the outermost filaments of the multifilament constituting the woven fabric of the obtained artificial leather was 3%, and although the artificial leather had a soft feel and excellent durability, polyvinyl alcohol was used, and the process load was higher than that of Example 1. The results are shown in Table 1.
[0183] [Table 1] [Industrial Applicability]
[0184] The artificial leather obtained by the present invention can be suitably used as an interior material having a very elegant appearance as a surface material for furniture, chairs, and wall materials, and for seats, ceilings, and interiors in vehicle cabins such as automobiles, trains, and aircraft; uppers and trims of shoes such as shirts, jackets, casual shoes, sports shoes, men's shoes, and women's shoes; bags, belts, wallets, and the like; and industrial materials used in parts of these materials, such as wiping cloths, polishing cloths, and CD curtains. [Explanation of symbols]
[0185] 1: Multifilament that makes up the fabric 2: Polyurethane 3: Filament with polyurethane attached 4: Filament with no polyurethane attached
Claims
1. An artificial leather comprising a fibrous base material formed by entangling and integrating a nonwoven fabric and a woven fabric, and a polyurethane having a hydrophilic group, The nonwoven fabric is composed of polyester ultrafine fibers having an average single fiber diameter of 0.1 μm or more and 10.0 μm or less, The woven fabric is composed of a multifilament having 30 to 300 filaments, and the average single fiber diameter of the filaments constituting the multifilament is 1 μm to 30 μm, The content of the polyurethane in the artificial leather is 15% by mass or more and 25% by mass or less, and the ratio of filaments to which the polyurethane is attached among the outermost filaments of the multifilament is 10% or more and 80% or less. Artificial leather.
2. 2. The artificial leather according to claim 1, wherein the polyurethane is a polyether-based polyurethane and / or a polycarbonate-based polyurethane.
3. The method for producing the artificial leather according to claim 1, comprising the following steps (1) to (3) in this order: (1) A process of entangling and integrating a nonwoven fabric made of ultrafine fiber-developing fibers with a woven fabric to form a fibrous substrate. (2) A process for obtaining a shrunk sheet having a width of 0.85L or more and 0.95L or less, in which the width of the fibrous base material before impregnation is L, by impregnating the fibrous base material with an aqueous dispersion of polyurethane having a hydrophilic group and then coagulating the polyurethane to obtain a sheet. (3) A step of expressing polyester ultrafine fibers from the ultrafine fiber-expressing fibers of the shrink sheet
4. The method for producing an artificial leather according to claim 3, wherein the entanglement and integration means in the step (1) is a needle punching process.
5. 5. The method for producing an artificial leather according to claim 3, wherein the means for obtaining the shrink sheet in the step (2) is a dry heat treatment at an atmospheric temperature of 100° C. or higher and 180° C. or lower.
6. The method for producing an artificial leather according to claim 3 or 4, wherein the means for developing the polyester ultrafine fibers in the step (3) is an alkali treatment.
7. An automobile interior material comprising the artificial leather according to claim 1 or 2.
8. An automobile part comprising the artificial leather according to claim 1 or 2.
9. A seat comprising the artificial leather of claim 1 or 2.
Citation Information
Patent Citations
Sheet-like material, method for producing the same and interior material, textile material and industrial material each using the same
JP2008075237A
Method for producing sheet-shaped material
JP2014025165A
Sheet-like object
JP2019044292A
Fiber sheet and manufacturing method of artificial leather using the fiber sheet
JP2022038822A
Napped artificial leather
WO2021049413A1